A Multiuser Subcarrier and Power Allocation Scheme to Improve the Performance of Cell Edge Users - Jianwu Zhang; Fang Li; Fangmin Xu (Dianxin kexue)
In the OFDMA system，the communication quality of cell edge users decline seriously，due to the same frequency interference from the adjacent cells. To restrain the inter cell interference effectively and greatly enhance the performance of wireless networks especially the performance of cell edge users is one of the goals of 5G mobile communication system. Based on the rate adaptive（RA）criterion，a joint resource allocation algorithm to improve the performance of cell edge users was proposed. The algorithm was separated into two steps with subcarrier and hybrid power allocation respectively. The proposed scheme could maximize link capacity with the consideration of the performance of cell edge users. The simulation results show that the edge user throughput is greatly increased，the throughput of system of mixed power distribution approximation is approximate to the throughput that all users use liner water-filling algorithm. Besides，the proposed scheme reduces the computation complexity.